Influence of microbial communities on the chemical and sensory features of Falanghina sweet passito wines. (June 2019) - De Filippis, Francesca; Aponte, Maria; Piombino, Paola; Lisanti, Maria Tiziana; Moio, Luigi; Ercolini, Danilo; Blaiotta, Giuseppe
Abstract: Natural (N) as well as starter inoculated (S, inoculated with Saccharomyces cerevisiae M3–5; CZS, Candida zemplinina T13, Zygosaccharomyces bailii NS113 and Saccharomyces cerevisiae M3–5) fermentations of Falanghina must from dehydrated grape were monitored. Culture dependent analyses and amplicon-based high-throughput sequencing targeting 18S rRNA and 16S rRNA genes were used to monitor the fungal and bacterial communities (8 sampling points during 65 days). The resulting wines were subject to both sensory evaluation and volatile organic compounds analysis. Fungal community of un-inoculated musts (N) at beginning of the fermentation was mainly represented by Aureobasidium, Cladosporium, Sclerotinia, while Candida, Debaryomyces, Hanseniaspora, Metschnikowia, Pichia, Saccharomyces and Zygosaccharomyces showed a very low occurrence. The dominance of Hanseniaspora vineae and/or Hanseniaspora uvarum was clear up to 29th days of fermentation. S. cerevisiae occurred in all the phases but become dominant only at the end of the process . The odour profiles as evaluate by Quantitative Descriptive Analysis (QDA) highlighted a significant impact of the fungal populations on the olfactory profiles of the wines. Raisins, dried fruits, Sherry and liqueur were stronger in both S and CZS, while N was mostly discriminated by solvent/chemical and floral features. Outcomes underpin the impact of microbiota on the chemical and odour traits of Falanghina passito wines. Graphical abstract: Unlabelled Image Highlights: Natural as well as starter-led fermentations of Passito from Falanghina wine grapes were monitored Natural fermentation was mainly carried out by H. uvarum and H. vinae until 29 days, when S. cereviasiae become dominant. The natural yeast microflora is inadequate to efficiently carry out the fermentative process. QDA highlighted a significant impact of fungal populations on wines sensory traits The use of selected starter cultures is confirmed as an optimal solution for passito wines production.